Reward dan Punishment sebagai Alternatif Mengatasi Perpindahan Aktivitas Pemerintahan di Ibukota Baru - Purwanto Purwanto (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2021)
This study aims to determine the strategy to overcome the transfer of PNS/ASN activities in the capital city of the new country. Qualitative methods are applied through literature review, documentation, and interviews. A total of 18 people consisting of practitioners, government, academics, communities, and the media (pentahelix model) were involved in information retrieval. The results showed that rewards and punishment can encourage someone to work as needed. Issues of incentives, facilities and infrastructure, development acceleration, employee selection, and application of regulations must be a concern of the government so that goals are achieved. Implementation of Law No. 43/1999 and Law no. 5/2014 can discipline disobedient employees through sanctions. A productive, competitive, and innovative young age can be prioritized to realize process and service optimization. The mental readiness of the next generation will be higher than that of the older generation when viewed psychologically.